Artificial intelligence in perspective - Bobrow, Daniel G. 1935- (MIT Press, 1994)
This collection of essays reviews the scope and progress of research in artificial intelligence over the past two decades. Seminal and most-cited papers from the journal "Artificial Intelligence" are revisited by the authors who describe how their research has been developed since publication.
"A Bradford book."
Reprinted from Artificial intelligence, an international journal, vol. 59, nos. 1-2, 1993.
Keywords: Artificial intelligence.; elektronické knihy; electronic books